Assessing the Performance Characteristics of Chicken Layers Fed with Pito Mash Inclusion Diets Treated with Cocoa Pod-Husk Ash Extract - Ankrah , Asare-Bediako; Donkoh, A.; Abando-Sam, Esther (International Journal of Poultry Science, 2014)
A nutritional balance trial was conducted, with 176 strain of Lohmann breed of brown layers at 8 weeks old, weighing between 340-341 g. The chickens were grouped into 4 dietary treatments of 44 chickens per group. A complete randomized design (CRD) was applied in which the dietary treatments included 0, 5, 10 and 15% level of the alkali-treated pito mash. Feed and water were provided ad libitum over the 11-month experimental period. The parameters measured were body weight changes, feed intake, water intake, hen-day egg production, hen-housed egg production, feed conversion ratio (kg/dozen egg), age at the onset of egg production, body weight at the onset of egg laying, weight of the first egg laid, shell thickness, number of broken egg, yolk colour, yolk diameter, albumen height, Haugh unit and mortality rate. Results showed that apart from body weight at the start of feed trial, feed/dozen eggs and body weight at the onset of egg laying, shell thickness and mortality of chickens, all the alkali-treated pito mash based diets exhibited significantly (p